Sierra - Siebert, Diane; Minor, Wendell ([New York] : HarperCollins, 1991)
One of the Sierra Mountains speaks of the beauty and timelessness of herself and her sister peaks.
6.3
K-3
K-3
Wilson's Children
Elem. School Library Collection
School Library Journal starred
Keywords: Children's poetry, American; Mountains -- Poetry; American poetry; Mountains -- Poetry; American poetry; Sierra Nevada (Calif. and Nev.) -- Poetry; Sierra Nevada (Calif. and Nev.) -- Poetry